Wireless sensor networks based efficient drip irrigation monitoring systems - Ashok, Karthik Sagar; Nagendrappa, Basavaraj Gangasamudra; Anjaneyalu, Mohan Bangalore; Nandihal, Priya; Reddy, Veena Narayana; Syed, Liyakathunisa; Noor, Ayman (International Journal of Electrical and Computer Engineering (IJECE), 2025)
Cotton has profound significance in the textile industry due to its versatility, comfort and ease of care. But the main problem with conventional cotton farming is that it uses more water. These issues are made more difficult by conventional irrigation methods, such as drip irrigation. To address this problem researchers are using traditional farming techniques with advanced wireless sensor network (WSN) protocols to resolve catastrophic issues, such as pipe bursts or blocked emitters which are detected early to save the water. This paper introduces efficient WSN architecture using priority-based directed information sharing (DIS) protocol for efficient utilization of water. The proposed architecture was implemented using TinyOS sensor network (TOSSIM) simulators. Exceptional quality of service (QoS) is achieved using new routing protocol exclusively for catastrophic failures. The proposed architecture is compared with standard protocols such as topology geographic greedy forwarding (TPGF), link carrier sense avoidance (LinkCSA) and tiny carrier sense avoidance (TinyCSA). Due to implementation optimized priority, DIS latency has been reduced from 11.3% to 11.02% and packet delivery ratio (PDR) is enhanced by 35% to 78% concerning benchmark protocols. The experimental results proves drastic improvement in PDR and delay performance as compared to the existing WSN protocol.